Penghindaran Pajak, Karakteristik Dewan Komisaris dan Cost Stickiness - Mitha Dwi Restuti (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2023)
This study aims to examine the relationship between tax avoidance and cost stickiness. This study also tests whether the relationship between tax avoidance and cost stickiness varies with the characteristics of the board of commissioners. The characteristics of the board of commissioners used are the size of the board of commissioners and the educational background of the board of commissioners. The study was conducted on listed firms on Indonesia Stock Exchange for the period 2013-2017. The results showed that there was a positive relationship between tax avoidance and cost stickiness. This study did not find enough evidence that the relationship between tax avoidance and stickiness costs was more positive in firms with a small size of the board of commissioners compared to large ones. Firms with a small size of board of commissioners indeed show anti-sticky costs and tax avoidance is not related to cost stickiness, but firms with a large board of commissioners show that there is a positive relationship between tax avoidance and cost stickiness. This study also found that in groups with small proportions of economic education / business background of board members there was a positive relationship between tax avoidance and cost stickiness, whereas in large groups there was no cost stickiness and found no relationship between tax avoidance and cost stickiness.